The Influence of Digital Transformation On The Performance of Culinary SMEs in Bogor District Using The Technology Organization Environment (TOE) Model - Putro, Andika Dwi; Cahyadi, Eko Ruddy; Anggraini, Elisa (School of Business, IPB University (SB-IPB), 2025)
Background: The culinary sector within SMEs in Bogor District has experienced rapid digital transformation. Key advancements include the adoption of digital payments, enhanced operational efficiency, and increased use of social media for marketing, supported by training initiatives aimed at improving service quality.Purpose: This study aims to analyze the factors that influence technology adoption among culinary SMEs in Bogor District and assess the impact of digital transformation on their performance.Design/methodology/approach: Utilizing the Technology-Organization-Environment (TOE) framework, this study evaluates factors affecting digitalization in culinary SMEs. Data were collected from 125 culinary SME respondents in Bogor District through online and in-person surveys, with purposive sampling. Analysis was conducted using Structural Equation Modeling - Partial Least Squares (SEM-PLS).Findings/Results: Out of four tested hypotheses, two yielded significant results. Organizational factors were positively associated with digitalization, while technological factors were not. Although environmental factors were not significant, digitalization demonstrated a positive impact on SME performance. Critical factors in the digital transformation process include the use of digital promotional media and digital payment systems, with sales growth and profitability emerging as indicators of SME success.Conclusion: Organizational factors, along with digital tools such as promotional media and payment systems, play a pivotal role in the successful digital transformation of culinary SMEs. Despite the non-significance of certain factors, digitalization remains a key driver of performance improvement.Originality/value: This study contributes to the understanding of digital transformation in the culinary SME sector, highlighting the role of organizational support and digital strategies in fostering growth and competitive advantage in the digital economy. Keywords: Culinary SMEs, Digital Transformation, Environment, Organization, Technology